This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For the floor and ceiling functions, for n ∈ N , − 1 < ϵ < 1 , we have that ⌊ n + ϵ ⌋ = n + ⌊ ϵ ⌋ and ⌈ n + ϵ ⌉ = n + ⌈ ϵ ⌉ .
Let's work our way from the inside out:
First of all, ⌈ 2 . 5 ⌉ = 3
Next, ⌊ 3 + 0 . 1 ⌋ = 3
Next, ⌈ 3 − 0 . 2 ⌉ = 3
See a pattern? We can use the property above to prove it:
First, we rewrite ⌈ ⌊ . . . ⌈ ⌊ 3 + 0 . 1 ⌋ − 0 . 2 ⌉ + 0 . 3 ⌋ − . . . − 1 ⌉ as ⌈ 3 + ⌊ 0 . 1 ⌋ + ⌈ − 0 . 2 ⌉ + . . . + ⌊ 0 . 9 ⌋ − 1 ⌉
The floor sends a number between 0 and 1 to 0 and the ceiling sends a number between -1 and 0 to 0, so the expression simplifies to ⌈ 3 + 0 + 0 + . . . + 0 − 1 ⌉ = ⌈ 3 − 1 ⌉ = ⌈ 2 ⌉ = 2